Egalitarianism under Pressure: Toward Lower Economic Mobility in the Knowledge Economy? - Simen Markussen; Knut Røed (Institute of Labor Economics (IZA), 2017)
Based on complete population data, with the exact same definitions of family class background and economic outcomes for a large number of birth cohorts, we examine post-war trends in intergenerational economic mobility in Norway. Despite only mild fluctuations in standard rank-based summary statistics, we show that men and women born into the lowest parts of the parental earnings rank distribution have fallen considerably behind in terms of several quality-of-life outcomes, such as earnings rank, earnings share, employment propensity, educational attainment, and the establishment of a family. In particular, the prime-age employment rates of lower class sons have declined spectacularly, both because their rank outcomes have deteriorated and because the lowest ranks to an increasing extent have become associated with non-employment rather than low-wage employment. We provide suggestive evidence that higher educational requirements in the labor market has increased the importance of parental encouragement and support and thus enlarged the handicap of being born into a less resourceful family. There is no evidence whatsoever of a relative decline in the lower classes' cognitive abilities.
Keywords: J62; D63; J24; 330; intergenerational mobility; inequality; cognitive ability